2010
DOI: 10.1007/s11302-010-9183-x
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in cochleovestibular hair cells and afferent neurons

Abstract: Purinergic signaling in the mammalian cochleovestibular hair cells and afferent neurons is reviewed. The scope includes P2 and P1 receptors in the inner hair cells (IHCs) of the cochlea, the type I spiral ganglion neurons (SGNs) that convey auditory signals from IHCs, the vestibular hair cells (VHCs) in the vestibular end organs (macula in the otolith organs and crista in the semicircular canals), and the vestibular ganglion neurons (VGNs) that transmit postural and rotatory information from VHCs. Various subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
(85 reference statements)
0
8
2
Order By: Relevance
“…Previous studies have shown that both inner and outer hair cells express P2X 2 which mediate ATP-induced cationic currents (Housley et al, 1999;Järlebark et al, 2002). We found no expression of P2X 2 in the spiral ganglionic afferents that innervate the inner and outer hair cells, in disagreement with some immunohistochemical studies and dissociated patch clamp studies (Järlebark et al, 2002;Weisz et al, 2009;Ito and Dulon, 2010).…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies have shown that both inner and outer hair cells express P2X 2 which mediate ATP-induced cationic currents (Housley et al, 1999;Järlebark et al, 2002). We found no expression of P2X 2 in the spiral ganglionic afferents that innervate the inner and outer hair cells, in disagreement with some immunohistochemical studies and dissociated patch clamp studies (Järlebark et al, 2002;Weisz et al, 2009;Ito and Dulon, 2010).…”
Section: Discussioncontrasting
confidence: 87%
“…IHCs in the pre-hearing cochlea also express P2 receptors (Huang et al, 2010; Ito and Dulon, 2010) (Figure S4) and spontaneous depolarizations of IHCs are sensitive to P2 receptor antagonists (Tritsch et al, 2007). To assess whether K + release from ISCs is sufficient to depolarize IHCs without purinergic receptor activation, we activated TMEM16A directly by inducing a rise in intracellular Ca 2+ within ISCs.…”
Section: Resultsmentioning
confidence: 99%
“…While there has been an extensive analysis of P2X receptor expression both in the developing and mature cochlea across several species (for reviews, see [1,22]), and adenosine receptor and ecto-nucleotidase activity has been established [23][24][25]. The sites and mechanisms of action of P2Y receptor activity in the cochlea are still emerging.…”
Section: Introductionmentioning
confidence: 99%